2019
DOI: 10.1016/j.compstruct.2018.09.097
|View full text |Cite
|
Sign up to set email alerts
|

The elastic properties of composites reinforced by a transversely isotropic random fibre-network

Abstract: 2019. The elastic properties of composites reinforced by a transversely isotropic random fibre-network. Composite Structures 208 , pp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In order to enhance the auxetic behaviour (i.e., a large negative Poisson's ratio), a relatively high value of ⁄ is desired. The elastic properties of composites can be significantly affected by the Poisson's ratio of the matrix material [15][16][17], but are less sensitive to that of the reinforcement material (this may be because the volume fraction of the latter is usually much smaller). As almost all the singlephase solid isotropic materials have a positive Poisson's ratio, a very small Poisson's ratio is desired for the matrix material in order to enhance the auxetic behaviour of the composites.…”
Section: Model Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to enhance the auxetic behaviour (i.e., a large negative Poisson's ratio), a relatively high value of ⁄ is desired. The elastic properties of composites can be significantly affected by the Poisson's ratio of the matrix material [15][16][17], but are less sensitive to that of the reinforcement material (this may be because the volume fraction of the latter is usually much smaller). As almost all the singlephase solid isotropic materials have a positive Poisson's ratio, a very small Poisson's ratio is desired for the matrix material in order to enhance the auxetic behaviour of the composites.…”
Section: Model Parametersmentioning
confidence: 99%
“…With the advance in materials syntheses, experimental measurements and computational simulations, it has been recognised that Poisson's ratio is related to the densification, connectivity, ductility and the toughness of solid materials [14]. It has also been found that the elastic properties of a composite material can be largely affected, thus tuned by the Poisson ratios of the constituent materials [15][16][17]. Cellular materials are often used as filler in sandwich structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many scholars have systematically studied the mechanical properties of discontinuous fiber reinforced composite through theoretical, experimental and numerical simulation methods [7,8]. The mean field inclusion method [9,10] or the micromechanical method [11,12] was adopted to predict the elastic modulus of discontinuous fiber reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…9 Natural and manmade fibers are manipulated by methods such as aligning, the formation of random networks, 10 knitting, 11 braiding, 12 weaving 13 and being applied to three-dimensional structures, 14 and are incorporated into the design of various structures to endow different abilities to the materials. Among these structures, random network structures based on mixed fibers provide high filterability, isotropic mechanical properties 15 and uniform density. 16 Therefore, determining how to control and form a uniform fiber network structure to optimize the desirable properties is significant for materials because the fiber dispersion effect is directly related to the final properties of the materials.…”
mentioning
confidence: 99%